2022
DOI: 10.2500/aap.2022.43.210107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for postviral olfactory dysfunction: A systematic review

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has been associated with a dramatic increase in postviral olfactory dysfunction (PVOD) among patients who are infected. A contemporary evidence-based review of current treatment options for PVOD is both timely and relevant to improve patient care. Objective: This review seeks to impact patient care by qualitatively reviewing available evidence in support of medical and procedural treatment options for PVOD. Systematic evaluation of data quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 78 publications
4
43
1
6
Order By: Relevance
“…A proportion of patients ( n = 37) were re-evaluated 2 months after the PRP injection, reporting significant improvements of ODQ and TDI scores. These data supported those of the preliminary study of Yan et al, who reported a substantial improvement of TDI scores in five out of seven patients [ 11 ]. The usefulness of PRP injection into the olfactory cleft was recently supported by Steffens et al [ 22 ] who observed that patients treated by PRP injection for a persistent (> 1 year) OD reported higher increase of TDI score improvements 1 month after the PRP injection compared with patients who did not benefit from injection.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A proportion of patients ( n = 37) were re-evaluated 2 months after the PRP injection, reporting significant improvements of ODQ and TDI scores. These data supported those of the preliminary study of Yan et al, who reported a substantial improvement of TDI scores in five out of seven patients [ 11 ]. The usefulness of PRP injection into the olfactory cleft was recently supported by Steffens et al [ 22 ] who observed that patients treated by PRP injection for a persistent (> 1 year) OD reported higher increase of TDI score improvements 1 month after the PRP injection compared with patients who did not benefit from injection.…”
Section: Discussionsupporting
confidence: 91%
“…The mean time of PRP extraction and injection found in the present study corroborated those of studies in which PRP procedure was performed for other otolaryngological indications [ 19 , 21 ]. The mean injected PRP amount was 1.2 mL/side, which was consistent with the data of Yan et al [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[ 18 ] At present, olfactory training is recommended as a first-line therapy for the treatment of PVOD, with topical corticosteroids, sodium citrate, oral vitamin A, and TCA considered as optional therapies for appropriately selected patients. [ 19 ] However, these treatments are sometimes ineffective. No high-level evidence are available to date on the efficacy of these measures in PVOD and further study is needed.…”
Section: Introductionmentioning
confidence: 99%